VARIETY OF SOUNDS AND WORDS IN T. SHEVCHENKO’S CREATION - Кононенко, І. В. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2020)
The article inquires into the variety of sounds and words in Taras Shevchenko’s poetic works. The ground for such effective use in Shevchenko is amplification – repetitions of language units of different types, which enables to realise artistic-aesthetic and pragmatic aims in their fundamental unity.